The Influence of Minority Stress, Gender, and Legalization of Civil Unions on Parenting Desire and Intention in Lesbian Women and Gay Men: Implications for Social Policy and Clinical Practice. Issue 1 (1st January 2019) - Scandurra, Cristiano; Bacchini, Dario; Esposito, Concetta; Bochicchio, Vincenzo; Valerio, Paolo; Amodeo, Anna Lisa
ABSTRACT: Although the rate of lesbian and gay (LG) parents is increasing, lesbian and gay adults are less likely than heterosexual adults to be parents, as desire and intention to become a parent tend to be lower. This study aims at assessing 290 childless LG individuals (120 lesbian women and 170 gay men) to explore the influence of minority stress, gender differences, and legalization of civil unions in Italy on parenting desire and intention. The results indicated that the minority stressors associated with parenting dimensions included prejudice events, outness, and internalized homophobia for lesbian women, but only felt stigma among gay men. Support from family or significant others buffered the effects of minority stressors on parenting dimensions. Thus, the minority stress processes partly explain the intention and desire to become parents in LG childless individuals. Furthermore, lesbian women showed higher levels of parenting desire and intention than gay men and the levels of these parenting dimensions increased after the law on civil unions was enacted. The findings have important implications for both social policies and clinical practice.